Optimizing Digital Marketing Through Facebook Marketplace for MSMEs in Wamena City: Opportunities, Constraints, and Strategic Adaptation - Difinubun, Muhamad Fagi (Unisia, 2025)
This study examines how micro, small, and medium enterprises in Wamena City, Highland Papua Province, Indonesia optimize digital marketing through Facebook Marketplace to overcome geographic isolation and expand their economic opportunities. The research aims to understand the extent of adoption, the strategies employed, and the barriers faced by entrepreneurs in this peripheral economy. A qualitative descriptive design was employed, drawing on semi-structured interviews with business owners and secondary data from scholarly and policy sources. Data were analyzed thematically to capture lived experiences, contextual challenges, and adaptive practices. The findings show that Facebook Marketplace and WhatsApp are the dominant platforms, enabling vendors to broaden market access, reduce spoilage of perishable goods, and enhance consumer engagement. Coffee producers, food vendors, and handicraft sellers reported tangible improvements in sales and visibility, supported by creative content and prompt customer interactions. However, weak internet infrastructure, uneven connectivity, and limited digital literacy hinder optimal use of advanced features such as targeted advertising and analytics. Training initiatives by government agencies, universities, and NGOs partially mitigate these gaps but remain inconsistent and unsustained. The discussion situates these findings within theoretical frameworks including the Resource-Based View and Dynamic Capabilities, underscoring how local enterprises adapt digital strategies under structural constraints. This study contributes to the literature by providing a context-specific account of digital marketing in a geographically remote region, highlighting both opportunities and limitations. The results carry practical and policy implications, emphasizing the need for infrastructure investment, continuous digital literacy training, and tailored support to ensure inclusive and sustainable digital transformation.